2017
DOI: 10.1016/j.ttbdis.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A comparative test of ixodid tick identification by a network of European researchers

Abstract: This study reports the results of a comparative test of identification of ticks occurring in Western Europe and Northern Africa. A total of 14 laboratories were voluntarily enrolled in the test. Each participant received between 22 and 25 specimens of adult and nymphal ticks of 11 species: Dermacentor marginatus, D. reticulatus, Haemaphysalis punctata, Hyalomma lusitanicum, Hy. marginatum, Ixodes ricinus, I. hexagonus, Rhipicephalus annulatus, R. bursa, R. rossicus, and/or R. sanguineus s.l. Ticks were morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…between different tick species are limited by spatial and temporal tick species distribution. The misidentification rate of ticks based on morphological features in our study was similar to that reported for the genus Ixodes (14%; Estrada‐Peña et al, ). Although I. persulcatus occurs in part of the geographic range included in our study (e.g., Finland and Estonia; ECDC, ; Laaksonen et al, ), and its morphological distinction from I. ricinus in immature stages is difficult, none of the tested samples were identified as I. persulcatus by 16 rRNA sequencing.…”
Section: Discussionsupporting
confidence: 90%
“…between different tick species are limited by spatial and temporal tick species distribution. The misidentification rate of ticks based on morphological features in our study was similar to that reported for the genus Ixodes (14%; Estrada‐Peña et al, ). Although I. persulcatus occurs in part of the geographic range included in our study (e.g., Finland and Estonia; ECDC, ; Laaksonen et al, ), and its morphological distinction from I. ricinus in immature stages is difficult, none of the tested samples were identified as I. persulcatus by 16 rRNA sequencing.…”
Section: Discussionsupporting
confidence: 90%
“…The taxonomists of ticks could easily identify tick species spread in their country, but they have misidentification rates when they identify tick species imported from other countries [ 75 ]. Nowadays, the molecular approach becomes an important trend in the taxonomic of tick species to resolve the misidentification problems.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we aimed to identify the species of ticks currently infesting cattle across various agroecological zones of Uganda, as well as to provide a baseline investigation to a larger study on ticks and tick-borne diseases in Uganda (Malmberg and Hayer 2019 ). In order to achieve a more precise taxonomic classification of ticks in our study, we complemented the traditional morphotaxonomic approach with molecular techniques as recently suggested and applied in some studies (Brahma et al 2014 ; Ernieenor et al 2017 ; Estrada-Peña et al 2017 ; Estrada-Peña et al 2013 ). Molecular analyses were also done in order to provide sequence information for those tick species in Uganda that were not yet available in GenBank.…”
Section: Introductionmentioning
confidence: 99%